The Story of the Dopamine Transporter PET Tracer LBT-999: From Conception to Clinical Use - Chalon, Sylvie; Vercouillie, Johnny; Payoux, Pierre; Deloye, Jean-Bernard; Malherbe, Cécile; Le Jeune, Florence; Arlicot, Nicolas; Salabert, Anne-Sophie; Guilloteau, Denis; Emond, Patrick; Ribeiro, Maria-Joao (Frontiers in Medicine, 2019)
The membrane dopamine transporter (DAT) is involved in a number of brain disorders and its exploration by positron emission tomography (PET) imaging is highly relevant for the early and differential diagnosis, follow-up and treatment assessment of these diseases. A number of carbon-11 and fluor-18 labeled tracers are to date available for this aim, the majority of them being derived from the chemical structure of cocaine. The development of such a tracer, from its conception to its use, is a long process, the expected result being to obtain the best radiopharmaceutical adapted for clinical protocols. In this context, the cocaine derivative (E)-N-(4-fluorobut-2-enyl)2β-carbomethoxy-3β-(4’-tolyl)nortropane, or LBT-999, has passed all the required stages of the development that makes it now a highly relevant imaging tool, particularly in the context of Parkinson’s disease. This review describes the different steps of the development of LBT-999 which initially came from its non-fluorinated derivative (E)-N-(3-iodoprop-2-enyl)-2-carbomethoxy-3-(4-methylphenyl) nortropane, or PE2I, because of its high promising properties. [18F]LBT-999 has been extensively characterized in rodent and non-human primate models, in which its demonstrated its capability to explore in vivo the DAT localized at the dopaminergic nerve endings as well as at the mesencephalic cell bodies, in physiological conditions. In lesion-induced rat models of Parkinson’s disease, [18F]LBT-999 was able to precisely quantify in vivo the dopaminergic neuron loss, and to assess the beneficial effects of therapeutic approaches such as pharmacological treatment and cell transplantation. Finally recent clinical data demonstrated the efficiency of [18F]LBT-999 in the diagnosis of Parkinson’s disease.